Peran Fikih di Era Globalisasi: Tantangan dan Peluang dalam Menjaga Identitas Hukum Islam - Zali, Muhammad; Sibarani, Nurul Sahputri; Harahap, Maymira Inory; Khairunissa, Ica; Malau, Nayla Rayhani (Mediation : Journal of Law, 2024)
Globalization has a major impact on social, cultural, and economic life throughout the world, including in the field of Islamic law. Fiqh, as a legal system in Islam, is faced with major challenges in maintaining its relevance and sustainability amidst rapid global changes. This article aims to examine the role of fiqh in facing the challenges of globalization, as well as how fiqh can adapt to the times without sacrificing its basic principles. Some of the main focuses in this journal are the application of fiqh in a modern context, the role of fiqh in resolving contemporary social issues, and its contribution to the development of sharia economics in the global world.